DADAP (ERYTHRINA SUMBUBRANS) AS HINDU ETHNOMEDICINE FROM LONTAR USADHA TARU PRAMANA - Ni Ketut Sinarsih; Mery Ambarnuari; I Gusti Agung Ayu Kartika (INTERNATIONAL JOURNAL ON HINDU CULTURE, 2024)
Dadap (Erythrina sumbubrans), a plant native to Bali, has been one of the foundations of Balinese ethnomedicine and Hindu ceremonies for centuries. delves into the multifaceted role of Dadap in traditional healing practices and its cultural significance within Hinduism. The plant is characterized by its expansive green, heart-shaped leaves and vibrant red flowers, which are highly valued for their medicinal and spiritual properties. In Hindu ceremonies, Dadap is respected as "kayu sakti," a sacred wood believed to possess magical powers. Its leaves are used in various rituals, including the Pitra Yadnya and Dewa Yadnya ceremonies, where they serve as guiding woods to ensure the deceased find a favorable path to Brahman. The plant`s bioactivity and phytochemical composition have been extensively studied, revealing its potential as an anti-inflammatory, antimicrobial, antipyretic, and antimalarial agent. The Usada Taru Pramana Lontar, a traditional Balinese healing text, provides detailed information on the medicinal uses of Dadap. The text describes how the plant's leaves, bark, and roots can be used to treat various ailments, including fever, internal bleeding, and digestive disorders. Scientific studies have validated these traditional uses, demonstrating the efficacy of Dadap extracts in reducing body heat and alleviating pain. This article aims to contribute to the preservation of Balinese cultural heritage by examining the empirical and scientific evidence supporting the medicinal and spiritual significance of Dadap. It highlights the potential for modernizing traditional medicine practices in Bali, while also emphasizing the importance of understanding the phytochemical properties of the plant to ensure safe and effective use.